Pengaruh Firm Size, Leverage, Profitability, Dan Net Working Capital Terhadap Cash Holding - Riska Ayu Agustya Putri, Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to obtain empirical evidence about the effects of firm size, leverage, profitability, and net working capital on cash holding in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. This research used 85 samples and 255 data from manufacturing companies selected by the purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and processed using the Eviews 11 program. The result of this research indicate that firm size and leverage doesn’t effect cash holding. Profitability has positive effect on cash holding. Net working capital has negative effect on cash holding.